Stability analysis of glass fibre polyamide composite transmission tower. (December 2020) - Bhowmik, Chiranjit; Gupta, Krishanu; Chakraborti, Prasun
The cross-sectional degradation of steel transmission tower members due to corrosion has been one of the major issues in the transmission line system. The degradation of appearance of the material has also been seen because of corrosion. Therefore, there is a need for a less corrosive and high strength alternate material for transmission towers. It seems in recent years that alternate materials have been needed to replace steel which have low maintenance cost and good resistance to corrosion. The advantages of composite transmission towers are fire resistant, high stiffness, durability, high strength, moderate ductility, rigidity, easy to assemble and economical. The present study has made an effort to evaluate the performance of composite transmission tower. The glass fibre polyamide composite material has been used as a structural material. First, a finite element tower model of 132 KV has been set up in Structural Analysis and Design Software as glass fibre polyamide structural material as per transmission tower design guidelines (Code for Transmission tower design, IS 802.1.1.1995, Bureau of Indian Standards). Second, all the active loads like wind load on the body, wind load on conducting wires and ground wires, weight of conducting wires, weight of structure, weight of ground wires, weight of insulator and weight of line man with tools are calculated manually as per transmission tower design guidelines and applied in the finite element tower model. The stress distribution of the composite tower model has been simulated in Structural Analysis and Design Software and the results have been analysed. The broken wire condition (if one conductor is broken or earth wire is broken) has been innovatively considered in the present study. Results obtained in this article show that maximum induced stress on transmission tower member is less than the deign strength of glass fibre polyamide composite material. The glass fibre polyamide composite material has been found to be capable to withstand the maximum stresses induced due to different loading conditions considered in the study.